Adverse effect of anthropogenic activities on water quality of the Sungai Lembing - Syamim Nadiah, Mohd Najib (2015)
Water quality of the Sungai Lembing in Kuantan is influenced by anthropogenic activities. This river and its tributaries is important to human as water supply, domestic uses, fisheries, tourism and recreation. The characteristics of water quality in Sungai Lembing need to specify because it may affect the water quality of the river.The objectives of this study were to assess the water quality based on National Water Quality Standard (NWQS) and Water Quality Index (WQI) Malaysia and to identify the source of pollution for sustainable management in the Sungai Lembing. Water quality of Sungai Lembing is determined based on WQI and NWQS and the samples were collected at three different points and two sampling times. The parameters were divided into two types which were in situ measurement and laboratory measurement. Based on the concentration of pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Ammoniacal Nitrogen (NH-3N) and Total Suspended Solid (TSS), the surface water of the Sungai Lembing was found to be slightly polluted. It shows that the mid-stream of the river was discovered to be more polluted contrast with the down and upper stream. It was the evidence of higher anthropogenic activities at that part. In conclusion, the Sungai Lembing is slightly polluted and apparently it is not suitable for tourist spot and the authority should take action to make proper extensive of the water treatment.